Advanced Non-Destructive in Situ Characterization of Metals with the French Collaborating Research Group D2AM/BM02 Beamline at the European Synchrotron Radiation Facility - Gilbert André Chahine; Nils Blanc; Stephan Arnaud; Frédéric De Geuser; René Guinebretière; Nathalie Boudet (Metals, 2019)
The ability to non-destructively measure the structural properties of devices, either in situ or operando, are now possible using an intense X-ray synchrotron source combined with specialized equipment. This tool attracted researchers, in particular metallurgists, to attempt more complex and ambitious experiments aimed at answering unresolved questions in formation mechanisms, phase transitions, and magnetism complex alloys for industrial applications. In this paper, we introduce the diffraction diffusion anomale multi-longueur d’onde (D2AM) beamline, a French collaborating research group (CRG) beamline at the European Synchrotron Radiation Facility (ESRF), partially dedicated to in situ X-ray scattering experiments. The design of the beamline combined with the available equipment (two-dimensional fast photon counting detectors, sophisticated high precision kappa diffractometer, a variety of sample environments, continuous scanning for X-ray imaging, and specific software for data analysis) has made the D2AM beamline a highly efficient tool for advanced, in situ synchrotron characterization in materials science, e.g., single crystal or polycrystalline materials, powders, liquids, thin films, or epitaxial nanostructures. This paper gathers the main elements and equipment available at the beamline and shows its potential and flexibility in performing a wide variety of temporally, spatially, and energetically resolved X-ray synchrotron scattering measurements in situ.